THE CORRELATION BETWEEN STUDENTS’ INTEREST IN ENGLISH YOUTUBE CONTENTS AND THEIR VOCABULARY MASTERY AT PGRI UNIVERSITY OF BANYUWANGI - Dellarosa Veronika Rahayu; Nur Hasibin; Abdul Halim (LUNAR, 2022)
Interest is important because it will be a motivating force for encouraging students to learn. It is also an aspect of motivation building, a phenomenon that arises as a result of social interaction and student interaction in learning activities. This research was aimed at finding out whether there is correlation between students’ interest in English YouTube contents and vocabulary mastery. Furthermore, in this quantitative research, the researcher used correlation research design. The population of this research was fourth semester of students of English department of PGRI University of Banyuwangi. This study used a sample of 13 students from the 2019 class. The researcher gave questionnaires to know students’ interest in English YouTube contents, and test to know the students’ vocabulary mastery. The result of this research shows that there is no correlationm between students’ interest in English YouTube contents and vocabulary mastery. It is provided by the t ro = 0,05 and rtable = 0.552 with a standard of significant 95%. The value of correlation product moment is lower than r table (0,05 < 0.552). It found that rxy = 0.05 in r table on the interval 0.00 – 0.199. So, the null hypothesis (H0) of the research is accepted , but Ha is rejected. It means there is no correlation between Students’ Interest in English YouTube Content and Their Vocabulary Mastery at PGRI University of Banyuwangi.